2000
DOI: 10.1002/1099-1379(200009)21:6<627::aid-job43>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the antecedents of coping with an organizational acquisition: a structural assessment

Abstract: This study used Lazarus and Folkman's (1984) cognitive–phenomenological model of coping and Lazarus's (1991) theory of emotions to develop and test a model of how individuals cope with an organizational acquisition. The model identifies the origins and process used to select both problem‐focused and emotion‐focused coping strategies. Covariance structure analysis of data from 172 individuals indicated that problem‐focused coping was directly influenced by primary appraisal and negative emotion, while only cert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 54 publications
1
81
0
1
Order By: Relevance
“…It is often perceived negatively because the changes are seen as threats or injuries (Scheck and Kinicki, 2000). Other research (e.g., Fay and Frese, 2001;Luthans et al, 2007;Fugate et al, 2012) addresses organizational change from a different approach, stating that the perception of change, positive or negative, is an individual trait that is context-dependent.…”
Section: Emotions In Organizational Changementioning
confidence: 99%
See 2 more Smart Citations
“…It is often perceived negatively because the changes are seen as threats or injuries (Scheck and Kinicki, 2000). Other research (e.g., Fay and Frese, 2001;Luthans et al, 2007;Fugate et al, 2012) addresses organizational change from a different approach, stating that the perception of change, positive or negative, is an individual trait that is context-dependent.…”
Section: Emotions In Organizational Changementioning
confidence: 99%
“…Other research (e.g., Fay and Frese, 2001;Luthans et al, 2007;Fugate et al, 2012) addresses organizational change from a different approach, stating that the perception of change, positive or negative, is an individual trait that is context-dependent. Negative perceptions of change have given rise to great interest in organizational research, given its importance in the aftermath of organizational changes (e.g., Scheck and Kinicki, 2000;Weeks et al, 2004;Bankins, 2015). THE SIX EMOTIONAL STAGES OF ORGANIZATIONAL CHANGE 8 Kotter and Schlesinger (2008) found that employees react in one of three ways during organizational change: passively, aggressively or honestly.…”
Section: Emotions In Organizational Changementioning
confidence: 99%
See 1 more Smart Citation
“…Both business downsizing and expanding have been shown to influence employee well-being through the experience of stress, anxiety and burnout (e.g. Ferrie et al, 2008;Haruyama et al, 2008;Scheck & Kinicki, 2000;.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Griffin's work demonstrated that personality traits perception can influence work outcomes. Likewise, Scheck and Kinicki (2000) identified that individual difference in personality perceive an event in different ways based on their dispositions. Raja et al (2004) investigated moderating effects personality types (neuroticism, extraversion, conscientiousness, self-esteem, equity sensitivity and locus of control) on the relations of contract breach and possible work outcomes.…”
Section: Differing Reactions To Contract Breach: the Role Of Adversitmentioning
confidence: 99%